12 HIGH PATIENT ACTIVATION IS ASSOCIATED WITH CLINICAL REMISSION IN A LONGITUDINAL ANALYSIS OF A LARGE INTERNET BASED COHORT OF PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (18th January 2018) - Barnes, Edward L; Long, Millie D; Kappelman, Michael D; Martin, Christopher F; Sandler, Robert S
Abstract: Background: High levels of patient activation, defined as having the knowledge, skills, and confidence to effectively manage one's care, has been associated with improved outcomes in many chronic conditions. We sought to evaluate the association between patient activation and disease remission in patients with inflammatory bowel disease (IBD). Methods: We performed a prospective cohort study utilizing the Crohn's and Colitis Foundation of America (CCFA) Partners internet cohort. We administered the validated, 13-item Patient Activation Measure (®Insignia Health) to 1, 486 participants. We used bivariate analyses and multivariable logistic regression to evaluate the association between patient activation at baseline and clinical remission after approximately 6–12 months. Clinical remission was defined as a score of < or = 2 on the Simple Clinical Colitis Activity Index (SCCAI) for ulcerative colitis (UC) or a score of <150 on the Short Crohn's Disease Activity Index (SCDAI) for Crohn's disease (CD). Results: A total of 1, 082 participants (73%) had follow-up data available for analysis (65% CD and 35% UC) after a median of 189 days (interquartile range:183–209). After adjusting for educational status and other confounders (Table 1), patients with higher patient activation (level 3 or 4) were more likely to be in clinical remission at follow-up for both CD [adjusted odds ratio (aOR) 1.60, 95% Confidence Interval (CI): 1.00–2.57) and UC (aOR 2.23, 95% CI:1.19–4.15)]. Conclusions: In this prospective internet-based cohort of patients with IBD, we demonstrated a strong association between patient activation and clinical remission in follow-up evaluation. Although a relatively novel concept in IBD, patient activation appears to impact the disease course of patients with CD and UC. Given that tailored interventions can increase patient activation in other diseases, efforts to improve patient activation in patients with IBD have the potential to improve outcomes.